The Government's Efforts in Fulfilling the Accessibility of the Rights of Persons with Disabilities through Social Rehabilitation in East Java - Muhammad Kanda Setia Putra; Yana Syafriana Hijri; Muhammad Kamil (Universitas Teuku Umar, 2022)
One of the benchmarks for democracy in a government is considering the state's ability to fulfill and guarantee the rights of its citizens. The East Java Provincial Social Service carries out rehabilitation regularly, both inside and outside the orphanage through program activities carried out by the Social Rehabilitation Division of East Java Province. The purpose of this research is how the government's efforts to fulfill the accessibility of the rights of persons with disabilities through social rehabilitation in East Java. This research uses qualitative research with a case study approach. This study uses 2 data sources, namely primary data and secondary data. Primary data was obtained through interviews with the Social Service of East Java Province regarding the Government's Efforts in Fulfilling Accessibility of Rights of Persons with Disabilities through Social Rehabilitation in East Java, while secondary data was obtained through journals for persons with disabilities, journals on the role of the government towards persons with disabilities, operational instructions for the work of the social services of the Java province. East Java, books or documents about persons with disabilities as references and supporting elements relevant to fulfilling the accessibility of persons with disabilities in East Java. In general, several programs have had a very positive impact on people with disabilities, but several things made the program less effective, such as the uneven distribution of programs in various districts/cities in East Java due to the limited number of targets, and inadequate follow-up after the program implementation monitored.